Industrial design and artistic expression : the challenge of legal protection - Pasa, Barbara (Leiden, Netherlands : Brill, 2020)
The complex nature of industrial design, which combines functional and aesthetic elements, allows different modes of protection: cumulative, separate or partially overlapping regimes are applicable according to different legal systems. The legal framework is rapidly changing, especially in Europe where the principle of cumulation of a special sui generis regime for protecting industrial design with copyright rules has been established. In the last decade, national courts of some Member States conferred to the "cumulative regime" a peculiar meaning, other courts enforced design rights in line with the interpretation given by the Court of Justice of the EU. The copyright/design interface is presented here to a wider, non-specialist audience, taking as a starting point the notion of industrial design derived from design studies, on the border between art and science
1. The thin line of artistic speculation about design activity -- 2. Design as a projection of the identity of the nation in post-war states -- 3. Legal requirements for defining protectable design works -- 4. Parameters to define protectable works -- 5. Protecting works of design today: a wide variety of legal tools -- 6. Who is protected
Includes bibliographical references
Keywords: Design protection -- European Union countries; Industrial design -- Law and legislation